BISNIS MILITER PASCA ORDE BARU - NUR KHAIRUNISA SUGIARTO (Department of Governmental Science FISIP UNPAD, 2018)
After the fall of the Suharto regime, the TNI's existence as a socio-political force was sued by many parties. They assume that TNI should not occupy positions outside of Hankam that should be a portion of civilian groups. According to Bilveer Singh, in most western societies, the role of the military is essentially to support the political aspirations of society under civilian leadership. This statement is based on the opinion of Samuel P. Hutington who said that the majority of military professionals in the west accept civil power as a right that should exist. Therefore, when the military